Quality of the Physical Education Teacher’s Instruction in the Perspective of Self-Determination - Vergara-Torres, Argenis P.; Tristán, José; López-Walle, Jeanette M.; González-Gallegos, Alejandra; Pappous, Athanasios Sakis; Tomás, Inés (Frontiers in Psychology, 2021)
The teacher's instructions in physical education class have important implications for the psychological well-being of their students. The aim of this study was to analyze, under the postulates of the Self-Determination Theory, a model with the following sequence: the perception of the quality of the instructions (task presentation, amount of corrective feedback and its legitimate perception) generated by the physical education teacher, the satisfaction of the three basic psychological needs and the subjective vitality in young students. The participants were 890 students (462 male, 428 female) of primary level from the metropolitan area of Monterrey, Mexico, between ages 11 to 13 (M = 11.36; SD = 0.49). The structural equation modeling showed positive and significant associations in all model interrelations; that is task presentation and the amount of corrective feedback (B = 0.88, p < .001), and this in turn with legitimate perception (B = 0.81, p < .001); the legitimate perception of feedback and the satisfaction of the need for autonomy, competence and relatedness (B = 0.63, p < .001; B = 0.90, p < .001; B = 1.01, p < .001, respectively); finally, the satisfaction of the three psychological needs and the subjective vitality (B = 0.11, p < .01; B = 0.43, p < .001; B = 0.24, p < .001, respectively). Therefore, the importance of a quality task presentation, as well as providing corrective feedback based on support for autonomy, is evident so that students perceive it legitimately and thus facilitate the satisfaction of their basic psychological needs and in consequence, indicators of psychological well-being such as subjective vitality.